A Network of Regulations by Small Non-Coding RNAs: The P-TEFb Kinase in Development and Pathology - Ghanbarian, Hossein; Grandjean, Valerie; Cuzin, Francois; Rassoulzadegan, Minoo (Frontiers in Genetics, 2011)
Part of the heterodimeric PTEF-b element of the PolII transcription machinery, the Cdk9 kinase plays a critical role in gene expression. Phosphorylation of several residues in the polymerase is required for elongation of transcript. It determines the rates of transcription and thus, plays a critical role in several differentiation pathways, best documented in heart development. The synthesis and activity of the protein are tightly regulated in a coordinated manner by at least three noncoding RNAs. First, its kinase activity is reversibly inhibited by formation of a complex with the 334 nt 7SK RNA, from which it is released under conditions of stress. Then, heart development requires a maximal rate of synthesis during cardiomyocyte differentiation, followed by a decrease in the differentiated state. The latter is insured by microRNA-mediated translational inhibition. In a third mode of RNA control, increased levels of transcription are induced by small noncoding RNA molecules with sequences homologous to the transcript. Designated paramutation, this epigenetic variation, stable during development and hereditarily transmitted in a non-Mendelian manner over several generations, is thought to be a response to the inactivation of one of the two alleles by an abnormal recombination event such as insertion of a transposon.